Cave Associated Infection: An Issue in Tropical Medicine - Wiwanitkit, Viroj (Journal of Health Science and Medical Research, 2018)
Caves are interesting and attractive natural sites that visitors can enter and explore. Sometimes, the visitors come in contact with pathogens in the cave, resulting in cave associated infections. In this short article, the authors hereby summarize and discuss cave associated infections with special reference to tropical countries. There are many possible cave associated infections, such as histoplasmosis and rabies, which are considered serious health problems.